1985
DOI: 10.1126/science.2865810
|View full text |Cite
|
Sign up to set email alerts
|

A Glycophospholipid Tail at the Carboxyl Terminus of the Thy-1 Glycoprotein of Neurons and Thymocytes

Abstract: Cell surface molecules of eukaryotic cells have been considered to be integrated into the membrane bilayer by a transmembrane protein sequence. The Thy-1 antigen of rodent thymocytes and brain was the first eukaryotic membrane molecule for which biochemical data clearly suggested membrane integration via a nonprotein tail. Direct evidence is now presented showing that a glycophospholipid structure is attached to the carboxyl-terminal cysteine residue and that 31 carboxyl-terminal amino acids predicted from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
151
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(156 citation statements)
references
References 42 publications
4
151
1
Order By: Relevance
“…However, a preliminary attempt to demonstrate the CRD determinant on Thy-I was unsuccessful (C. Bordier and C. Bron, unpublished work). This might be because the glycolipid of Thy-I does not contain galactose, since the CRD determinant was also absent in a galactosedependent glycolipid anchor from trypanosomes [17,21]. Incorporation of [3H]myristate into VSG during a 2 min labelling period was also demonstrated [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a preliminary attempt to demonstrate the CRD determinant on Thy-I was unsuccessful (C. Bordier and C. Bron, unpublished work). This might be because the glycolipid of Thy-I does not contain galactose, since the CRD determinant was also absent in a galactosedependent glycolipid anchor from trypanosomes [17,21]. Incorporation of [3H]myristate into VSG during a 2 min labelling period was also demonstrated [23].…”
Section: Discussionmentioning
confidence: 99%
“…A few externally exposed plasma-membrane proteins from protozoan and mammalian origin, however, are anchored via a covalently attached glycolipid which contains phosphatidylinositol (PI), and these proteins can be released from the membranes by phospholipases C (PLC) [4,5]. The growing list of glycoproteins of this type comprises the variable surface glycoproteins (VSG) of trypanosomes [6,7], the p63 surface glycoprotein of Leishmania [8], the membrane forms of alkaline phosphatase [9], acetylcholinesterase [10], 5'-nucleotidase [ 1 1,12], the 120 kDa form of rodent neural-cell adhesion molecule ('NCAM') [13], and several immunologically relevant surface proteins such as decay-accelerating factor ('DAF') [14], the rat lymphocyte alloantigen RT-6.2 [15], the mouse Ly-6 antigen [16] and the Thy-I antigen of lymphocytes and brain cells [17,18]. Considerable chemical information exists about the membrane-anchoring glycolipid of VSG and Thy-i; amino-acid-sequencing studies revealed in both cases that the mature molecules lack a C-terminal stretch of hydrophobic amino acids predicted from the cDNA sequences [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that the Thy-1 antigens are anchored in the plasma membrane via a phospholipid, possibly one with a phosphoinositol domain (44,65). However, this hypothesis has been challenged by cDNA sequence analysis which suggests that a segment of 31 amino acids at the carboxyl terminus of the Thy-1 molecules may be responsible for the integration of this protein into the plasma membrane (21,57).…”
mentioning
confidence: 99%